Synthesis of Ammonium Silicate Liquid Fertilizer from Rice Husk Ash - Santi, Sintha Soraya; Pramuji, Faiq Hawaari Ahmad; Juventino, Syahdhan Adiyah Islami; Puspitawati, Ika Nawang (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to synthesise liquid ammonium silicate fertiliser ((NH?)?SiO?) from rice husk ash and to determine the effects of varying ammonium hydroxide (NH?OH) concentration and reaction temperature on the resulting silica (Si) and nitrogen (N) content. Rice husk ash is used as a silica source because it contains high levels of SiO?, up to 82%. The research process includes three main stages: raw material preparation; silica extraction using 10% NaOH at 80°C for 120 minutes; and a synthesis reaction between the extracted silica and an NH?OH solution (5–25%) at 30–110°C for 60 minutes. Silica content analysis was carried out using UV-Vis spectrophotometry, while nitrogen content was analyzed using the Kjeldahl method. The results showed that increasing NH?OH concentration and reaction temperature significantly increased silica content, while increasing temperature tended to decrease nitrogen content due to ammonia volatility. The best conditions were obtained at a NH?OH concentration of 25%, a reaction temperature of 70°C, a silica content of 5.2701%, and a nitrogen content of 17.1637%. The results meet the SNI 02-6681-2002 standard for liquid macro compound fertilizers, which requires a minimum content of 4% for silica and nitrogen. Thus, rice husk ash has great potential as an alternative raw material for the manufacture of environmentally friendly ammonium silicate liquid fertilizers. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action